2008
DOI: 10.1017/s0022215107001296
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of X-ray and computed tomography screening for assessing pulmonary involvement in patients with head and neck squamous cell carcinoma

Abstract: There is currently no consensus on the use of chest X-ray and computer tomography for screening newly diagnosed cases of head and neck squamous cell carcinoma. We recommend routine scanning of high-staged head and neck squamous cell carcinoma. The National Institute of Health and Clinical Excellence guidelines should be reappraised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Chest radiography is, however, likely to be out-dated, as previously shown by several groups [ 5 , 11 ]. Newer technologies now widely available such as computer tomography and positron emission tomography (PET/CT) are currently being evaluated as screening tools in HNSCC [ 4 , 5 , 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chest radiography is, however, likely to be out-dated, as previously shown by several groups [ 5 , 11 ]. Newer technologies now widely available such as computer tomography and positron emission tomography (PET/CT) are currently being evaluated as screening tools in HNSCC [ 4 , 5 , 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loh et al evaluated screening of patients with HNSCC using chest CT and found clinically T4 and/or N2/3 to be risk factors for the development of distant metastases. Leong et al found, in their series of 102 patients who underwent screening by chest X‐ray and chest CT, that of the patients with positive screening, 86% had clinically T3 or T4 disease and 71% had clinically N2 or N3 disease. In 21% of patients with clinically advanced‐stage disease (T3/4 and/or N2/3), Haerle et al detected distant metastases by positron emission tomography (PET)‐CT and follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…These figures were significantly higher as compared to patients with tumors at other sites and lower T-or N-classifications [10]. Leong et al [11] found in their series of 102 patients who underwent screening by chest X-ray and CT that of the patients with positive screening, 86% had T3 or T4 disease and 71% had N2 or N3 disease.…”
Section: Introductionmentioning
confidence: 89%